In detail : - Rainey de Diaz, Isobel (Thomson/Heinle, 2003)
IN DETAIL is a two-level integrated skills course designed to develop and solidify the language skills that intermediate and advanced learners need outside the English language classroom. Developed for a multiskills syllabus which integrates communicative, grammatical, and critical thinking objectives, IN DETAIL uses a spiraled approach to provide extensive review, reinforcement, and expansion of language skills. Need a six-level articulated series? Use IN DETAIL as a follow-up to the four-level UP CLOSE series and successfully guide your students from the beginning through the advance level!